Primary Amenorrhea in Kashmiri Adolescent Females - A Hospital Based Study - Rasool, Shubana; Hakeem, Aijaz; Shafi, Hakim; Mufti, Shahida (Nepal Journal of Obstetrics and Gynaecology, 2011)
DOI: http://dx.doi.org/10.3126/njog.v5i1.5054 NJOG 2010 Jul-Aug; 5(1): 12-16